Visible-light-driven photocatalytic H2 production from H2O boosted by anchoring Pt and CdS nanoparticles on a NaY zeolite. (29th June 2022) - Lv, Zhenhui; Liu, Peng; Zhao, Yiyi; Peng, Chong; Meng, Xin-Yu; Pan, Yun-Xiang
Graphical abstract: Highlights: Finely tuning on the structures of NaY zeolite is achieved by simply changing crystallization times. The NaY zeolite triggers more efficient separation of the photogenerated electron-hole pairs. The NaY zeolite leads to enhanced visible-light-driven photocatalytic H2 production from H2 O. Outstanding photocatalytic stability is obtained in the presence of the NaY zeolite. Abstract: Photocatalytic H2 production from H2 O is promising for solving the energy and environment problems. Zeolites have been widely used in thermocatalysis, but their application in photocatalysis is limited. Herein, we anchor CdS and Pt nanoparticles on a NaY zeolite (ZP48) fabricated via 48 h crystallization to form a CdS/Pt/ZP48 photocatalyst for visible-light-driven photocatalytic H2 production from H2 O. CdS/Pt/ZP48 shows a H2 production rate (686.5 μmol h −1 ) which is higher than those on Pt/CdS (263.2 μmol h −1 ) and photocatalysts with zeolite supports prepared by using crystallization times shorter and longer than 48 h, with an apparent quantum efficiency of 23.5% and superior stability. ZP48 promotes the separation of photogenerated electron-hole pairs, thus releasing more electrons for enhancing the photocatalytic H2 production on CdS/Pt/ZP48. These results are helpful for fabricating more efficient photocatalysts by zeolites which are widely used in industry but have poor ability in light absorption and charge transfer.